Limits to the Anthropocene: geopolitical conflict or cooperative governance? - Scheffran, Jürgen (Frontiers in Political Science, 2023)
In the Anthropocene the world is facing an acceleration of human growth and its impact on nature. The expansionist world order which emerged from Europe since colonial times is reaching multiple limits (environmental, economic, social, political and scientific-technical), increasing marginal costs and risks which trigger multiple crises, conflicts and catastrophes that challenge this world order. Alternative futures range from a collapse of human civilization to geopolitical power competition and conflict between rivals to disruptive technical innovations and systemic transformation of the economy and society within natural boundaries. In response to geopolitical conflicts and their consequences, such as climate change and the Russia-Ukraine war, efforts of cooperative governance can help to mitigate, adapt to and manage complex crisis landscapes. Instead of an epochal turn (Zeitenwende) for arms race and war, more promising are sustainable climate protection and a peaceful energy transition within planetary boundaries. To further prevent escalating and mutually enforcing crisis dynamics and geopolitical conflicts in the Anthropocene, cooperative governance needs to adjust to the world's complexity and move from a negative nexus of problems to a positive nexus of solutions. The interaction between geopolitics and governance and the transition from risk cascades to synergies is discussed for the energy-security nexus and the climate-conflict-migration nexus. Energy conflicts can be contained by diminishing land competition and biodiversity loss, as well as risky dependencies on strategic raw materials and conflict minerals. Measures for a sustainable energy transition include energy efficiency and conservation, renewable energy and decarbonization, a circular economy and nature-based solutions. To prevent risk multiplication in the climate-conflict-migration nexus, synergies in climate, migration and security policy facilitate integrative solutions for a socio-ecological transformation based on mitigation and adaptation, conflict resolution and environmental peacebuilding, aiming for a mutual enforcement of sustainability and peace.